2011
DOI: 10.1002/pen.22154
|View full text |Cite
|
Sign up to set email alerts
|

Visual observation and numerical studies of N2 vs. CO2 foaming behavior in core‐back foam injection molding

Abstract: We investigated, by visual observation and numerical calculations, the foaming behavior of polypropylene within a foam injection mold cavity with the environmentally benign physical blowing agents nitrogen (N2) and carbon dioxide (CO2). An 85‐ton core‐back injection‐molding machine with temperature and pressure monitoring systems as well as a high‐pressure view cell was used for the investigation. The experiments showed a prominent difference in bubble nucleation and growth between N2 and CO2 injection foaming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 17 publications
(27 reference statements)
0
50
0
Order By: Relevance
“…Dissolved gas then starts emerging from the solution and generating bubbles inside of the molded part. 13 It has been reported that open porous polypropylene and polyether-urethane have been produced using microcellular injection molding. 14,15 The orthogonal array test is a systematic, statistical testing technique, which is particularly effective in finding errors associated with faulty logic within computer software systems.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved gas then starts emerging from the solution and generating bubbles inside of the molded part. 13 It has been reported that open porous polypropylene and polyether-urethane have been produced using microcellular injection molding. 14,15 The orthogonal array test is a systematic, statistical testing technique, which is particularly effective in finding errors associated with faulty logic within computer software systems.…”
Section: Introductionmentioning
confidence: 99%
“…observed the shift from elongated cells into circular cells in the direction parallel to the flow in the FIM. In addition, FIM can sometimes be accompanied by a controlled mold‐opening step which is also termed as breathing or core‐back to increase the void fraction . For example, Takeshi et al .…”
Section: Introductionmentioning
confidence: 99%
“…The location of the viewing windows in the fixed plate, on the opposite side of the mold cavity, makes it possible to perform various experiments by simply changing the mold insert, some of which includes, but is not limited to, gasassisted FIM studies, shear/extension induced FIM, and the study of flow in various channels. Also, the mold can be utilized to investigate other FIM technologies such as gas-counter pressure (GCP) [12,13] and mold opening (core back) [9,10,14,15]. The designed mold can be utilized to further investigate the mechanisms of bubble nucleation/growth, interaction between bubbles and fillers [16,17], the effect of formed crystals on foaming [18], weld-line studies [19], defects [20], and model verifications [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most of hypotheses or theoretical simulations were not experimentally verified [5,6]. In this context, the in-situ observation of foaming phenomena drew significant attention amongst researchers [7][8][9][10]. Villamizar and Han [7] designed a rectangular visualization mold with transparent quartz walls to investigate the bubbles' dynamics in conventional structural FIM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation